Introduction to Information Systems - O’Brien, James A (Mc Graw Hill, 2007)
The Thirteenth Edition is designed for business students who are or who will soon become business professionals in the fast changing business world of today. The goal of this text is to help business students learn how to use and manage information technologies to revitalize business processes, improve business decision making, and gain competitive advantage. Thus, it places a major emphasis on up-to-date coverage of the essential role of Internet technologies in providing a platform for business, commerce, and collaboration processes among all business stakeholders in today's networked enterprises and global markets. This is the business and managerial perspective that this text brings to the study of information systems.